The Effect of Grammar and Vocabulary Mastery toward English Writing Skills on Vocational High School Students in Serang - Sayyid Khairunas; Ary Iswanto Wibowo; Rizki Mirani Desi Pratama (Universitas Musamus Merauke, 2021)
The objective of this study is to see the effect of grammar and vocabulary mastery on writing in English. The research method used is a survey method with analysis and regression techniques with the assistance of the SPSS 20 program. The research sample examined 47 students from 3 high schools, namely students of class XI at SMK Daarul Hikmah, SMK Miftahul Falah and SMK Daruttaibin which are located at Serang Regency. The data set collection is accumulated by presenting a grammar mastery questionnaire by carrying out a written English proficiency test. From the analysis, result shows: 1) There is a significant effect of mastery of grammar and vocabulary together on the English writing skills of students at SMK in Serang Regency. It is indicated by the acquisition of the Sig. 0.000 <0.05 and FH = 49,615. Along with mastery of grammar and vocabulary contributed 69.3% to the variables written in English. 2) There is a significant effect of language mastery on the English writing skills of students at SMK in Serang Regency. It is proven by the acquisition of the Sig. 0.001 <0.05 and th = 3.616. The grammar mastery variable contributed 12.39% in improving English writing skills. 3) There is a significant effect of vocabulary mastery on the English writing skills of SMK students in Serang Regency. The acquisition of the Sig. 0,000 <0.05 and th = 6,093 is shown in the data. Vocabulary mastery variable contributed 35.28% in improving written skills in English.